Decellularized liver as a translucent ex vivo model for vascular embolization evaluation. (May 2020) - Gao, Yanan; Li, Zhihua; Hong, Yin; Li, Tingting; Hu, Xiaoyan; Sun, Luyao; Chen, Zhengchang; Chen, Zijian; Luo, Zhiheng; Wang, Xin; Kong, Jian; Li, Guanglei; et al.
Abstract: Transarterial chemoembolization (TACE) is the preferred treatment for patients with unresectable intermediate stage hepatocellular carcinoma, however currently the development of embolic agents for TACE lacks in vitro models that closely represent the sophisticated features of the organ and the vascular systems therein. In this study, we presented a new strategy using an ex vivo liver model to provide a translucent template for evaluating embolic agents of TACE. The ex vivo liver model was developed through decellularizion of rat liver organs with preserved liver-specific vasculatures and improved transmittance of the whole liver up to 23% at 550 nm. Using this model, we investigated the embolization performances of both liquid and particle-based embolic agents, including penetration depth, embolization end-points, injection pressure and spatial distribution dynamics. We found that the embolization endpoint of liquid embolic agent such as ethiodised oil was strongly dependent on the injection pressure, and the pressure quickly built up when reaching the capillary endings, which could cause embolic agent leaking and potential tissue damages. In contrast, for particle-based embolic agents such as poly-dl -lactide microparticles and CalliSpheres® beads, their embolization endpoints were mainly determined by the particle size, whereas the particle densities close to the endpoints dramatically dropped down, which with the penetration depth represented two critical factors determining the embolic distribution. Such a decellularized organ model may open a new route to visually and quantitatively characterize embolization effects of various embolotherapies.